Scarabaeoidea beetles (INSECTA: COLEOPTERA) of Calmeca, Tepexco, Puebla, Mexico - Carrillo-Ruiz, Hortensia; Guerra-González, Irma; Sánchez-Carrillo, Marcela; Morón, Miguel A.; Rivas-Arancibia, Sombra P. (Instituto de Ecología, A.C., 2017)
A comparative study of Coleoptera Scarabaeoidea in the community of Calmeca, Tepexco, Puebla, Mexico is presented. Samples of beetles were taken from November 2013 to November 2014 in a place with induced pasture land with neighboring crops (SP) and a site representative of deciduous forest with secondary vegetation (SC). By mean of necrotraps, rotten fruit traps and hand collecting, 945 specimens were obtained, representing 28 species in six families of Scarabaeoidea. The SP had the highest species richness with 27 species; the most abundant species was E. intermedius (30.19%) with 257 specimens, followed by D. gazella (14.33%) with 122 specimens. In the SC the most abundant species were C. (C.) humectus (20.21%) and C. (C.) pluto (20.21%) each with 19 specimens collected. No significant differences between the two sampling sites (p = 0.111) were found. The Calmeca beetle community was grouped in eight feeding guilds. At both sites most recorded species belong to the coprophagous guild (SP 37% & SC 53%), the necrophagous guild (SP 14.8% & SC 26.6%) and the phytophagous guild (SP 18% & SC 13%). The SP had a higher functional richness with eight guilds, compared with the SC with four guilds; in the SC no species of predator, antophilous, and rhizophagus guilds were recorded.